Calcium Complexes Having Different Amidinate Ligands ‐ Synthesis and Structural Diversity. Issue 9 (27th June 2016) - Anga, Srinivas; Bhattacharjee, Jayeeta; Banerjee, Indrani; Nayek, Hari Pada; Panda, Tarun K.
Abstract: A one‐pot reaction of α‐diimine ligand 1, 4‐disubstituted diazabutadienes (DAD) with potassium benzyl and anhydrous calcium iodide in 1:1:1 molar ratio afforded unprecedented 3‐phenylprop‐2‐ene‐di‐amido calcium compound [ κ 2 ‐(THF)4 CaDippNC(=CHPh)CH2 NDipp] (1 ) (Dipp = 2, 6‐diisopropylphenyl) in good yield. The solid‐state structure of the compound1 revealed the formation of dianionic 3‐phenylprop‐2‐ene‐di‐amido ligand having an exocyclic olefinic bond derived from neutral α‐diimine fragment. However, analogous reactions with three different carbodiimides (RN=C=NR; R=Cy, iPr and t Bu) with alkyl potassium and anhydrous calcium diiodide yielded corresponding homoleptic calcium compounds with amidinato ligand [ κ 2 ‐(THF)2 CaRN=C(CH2 Ph)NR2 ] [R=Cy (2 ), i Pr (3 ) and t Bu (4 )]. A separate reaction of DAD ligand, LiCH2 SiMe3 and anhydrous ZnCl2 in diethylether solvent produced tri‐coordinated zinc compound [ κ 2 ‐ DippN=C(CH2 SiMe3 )CH2 NDippZn[ κ 1 ‐DippN=C(CH2 SiMe3 )CH2 N‐Dipp] (5 ) having amidinato moieties in the zinc coordination sphere in high yield. Molecular structures of compounds2–5 in their solid states were also established. Abstract : A one pot reactions of anhydrous calcium iodide potassium benzyl either with 1, 4‐ diazabutadienes ( Dipp DAD) or three different carbodiimides (RN=C=NR; R=Cy, iPr and t Bu) have been demonstrated and their structural diversity are reported.